Meta-analysis of Oncogenic Protein Kinase Cι Signaling in Lung Adenocarcinoma - Erdogan, Eda (2009)
PURPOSE: Atypical protein kinase Cι (PKCι) is an oncogene in non – small cell lung cancer (NSCLC). Here, we identify four functional gene targets of PKCι in lung adenocarcinoma (LAC), the most prominent form of NSCLC. EXPERIMENTAL DESIGN: Three independent public domain gene expression data sets were interrogated to identify genes coordinately expressed with PKCι in primary LAC tumors. Results were validated by QPCR in an independent set of primary LAC tumors. RNAi-mediated knockdown of PKCι and the target genes was used to determine whether expression of the identified genes was regulated by PKCι, and whether these target genes play a role in anchorage-independent growth and invasion of LAC cells. RESULTS: Meta-analysis identified seven genes whose expression correlated with PKCι in primary LAC. Subsequent QPCR analysis confirmed coordinate overexpression of four genes (COPB2, ELF3, RFC4, and PLS1) in an independent set of LAC samples. RNAi-mediated knockdown showed that PKCι regulates expression of all four genes in LAC cells, and that the four PKCι target genes play an important role in the anchorage-independent growth and invasion of LAC cells. Meta-analysis of gene expression data sets from lung squamous cell, breast, colon, prostate, and pancreas carcinomas, as well as glioblastoma, revealed that a subset of PKCι target genes, particularly COPB2 and RFC4, correlate with PKCι expression in many tumor types. CONCLUSION: Meta-analysis of public gene expression data are useful in identifying novel gene targets of oncogenic PKCι signaling. Our data indicate that both common and cell type – specific signaling mechanisms contribute to PKCι-dependent transformation.